2018
DOI: 10.22146/ijbiotech.32332
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization and detoxification of batik dye effluent containing Indigosol Blue-04B using fungi isolated from contaminated dye effluent

Abstract: Fungi are capable of treating various synthetic dye effluents. Previously, we isolated seven strains of fungi from contaminated batik dye effluent at Banyumas, Central Java. The aims of this study were to screen the ability of these fungi to decolorize batik dye effluents containing Indigosol Blue-04B and to investigate the phytotoxicity effects of biodegraded effluent on the germination of corn seeds Zea mays L. and green bean seeds Vigna radiata (L.) Wilczek. In addition, the decolorized effluents were teste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
0
7
0
3
Order By: Relevance
“…Loss of color is an obvious indicator of dye removal from solutions but the assessment of products or metabolites; their chemical nature and further evaluation of toxicity become essential (Khandare & Govindwar 2015). Dewi et al (2018a) reported that Aspergillus sp. 3 was the best isolate for decolorizing the effluent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of color is an obvious indicator of dye removal from solutions but the assessment of products or metabolites; their chemical nature and further evaluation of toxicity become essential (Khandare & Govindwar 2015). Dewi et al (2018a) reported that Aspergillus sp. 3 was the best isolate for decolorizing the effluent.…”
Section: Discussionmentioning
confidence: 99%
“…Hefnawy et al (2017) reported the fungi decolorization of dye could be achieved by treating with Aspergillus flavus and Aspergillus niger. Dewi et al (2018aDewi et al ( , 2019a reported Aspergillus sp. 3 could decolorize batik effluent at 24 h, and its degradation products did not cause any toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Aktivitas penurunan kadar lemak juga telah memperbaiki kondisi limbah, sehingga telah memenuhi baku mutu bangan air limbah untuk industri tekstil. Pembuangan limbah secara langsung ke badan air tanpa pengolahan secara lanjut akan menyebabkan polusi pada lingkungan dan bersifat toxic bagi organisme yang hidup di lingkungan perairan (Dewi et al 2018). Polusi pada air tanah dan badan air biasanya disebabkan oleh proses industrialisasi serta urbanisasi yang semakin berkembang, ditambah tidak memperhatikan efek sampingnya terhadap konsekuensi lingkungan (Sundar et al, 2010).…”
Section: Pendahuluanunclassified
“…Several physicochemical methods have been applied for textile wastewater treatment, such as electrochemical oxidation , adsorption using chitin-based adsorbent [Wang et al, 2020], and Khamir (Saccharomyces cerevisiae) as adsorbent of Remazol Red RB textile dyes [Sukarta et al, 2021], and photocatalytic method using TiO 2 /UV-irradiation [Azzaz et al, 2021]. The biodegradation methods used for textile wastewater treatment included microalgae [Daneshvar et al, 2007;El-Sheekh et al, 2018;Premaratne et al, 2021], bacterial consortia attached growth reactor [Iqbal et al, 2022],and fungi [Dewi et al, 2018;Salem et al, 2019;Mahmood et al, 2021]. Among these methods, the biological method, mainly using wood-degrading fungi, has attracted much attention as one of the efficient techniques for removing color from dyes due to their environmentally friendly, cost-competitive, easy operation, and high color removal efficiency.…”
Section: Introductionmentioning
confidence: 99%